TURP VE TRANSVEZİKAL PROSTATEKTOMİ AMELİYATLARININ SEKSÜEL FONKSİYON ÜZERİNE ETKİSİ - ÖZKARA, Hamdi; ALICI, Bülent; AKKUŞ, Emre; ATAUS, Süleyman; HATTAT, Halim (Cerrahpaşa Medical Journal, 2019)
Background and Design. Erectile function of 105 men who underwent prostatectomy (transurethral or transvesical) for benign prostatic enlargement was assessed before and after operation in a prospective study. Results. Six months after the operation only 80 of them were available for evaluation. Preoperatively, 22 could not maintain their erections to achieve coitus. Six months after operation a decrease in erection had been experienced by 18 of remaining 58 patients, while 1 with erectile dysfunction before surgery declared an improvement. Conclusion. Prostatectomy operations had negative effect on erectile function of men, and there is no significant difference between both procedures.